VOLUME CHANGE AND COMPRESSIVE STRENGTH OF COMPACTED LATERITIC SOIL UNDER DRYING-WETTING CYCLE REPETITION - Zubair Saing; Marshus Hi Ibrahim; Irianto (GEOMATE Journal, 2020)
This study was conducted to investigate volume changes and compressive strength behavior of compacted high expansive soils from lateritic soils (60%) and bentonite (40%) mixture under drying-wetting cycle repetition as a construction materials alternatives. Lateritic soil obtained from waste Nickel mining site in East Halmahera, North Maluku, Indonesia. Laboratory tests of physical properties using ASTM standard test were conducted to lateritic soil, bentonite, and mixture soil, while SEM test for lateritic and mixture soil. The soil samples have optimum moisture content based on Proctor standard compaction test results (28%). Then, samples were treated drying-wetting cycle and repeating four cycles with 25, 50, 75, and 100% series path. The soil suction measurement used the Whatman #42 filter paper placed at the top, middle, and bottom of each sample, and after that, the unconfined compression strength test was performed based on the ASTM standard. The experimental results showed that the drying-wetting cycle repetition has a significant effect on volume change, suction, and compressive strength of the soil. The increasing number of cycle causing void ratio decrease and degree of saturation increase, and soil suction tend to decrease at the certain void ratio; likewise, soil compressive strength decreases at particular water content. Decreasing soil compressive strength causes a decrease in elastic modulus so that soil failure behavior is more brittle and work-softening. Therefore, the study results provide important geotechnical characteristics data of lateritic soil with high swell-shrink potential. Henceforth, some soil improvement innovations can perform to generate high-quality construction materials more effectively and efficiently.